Negotiation analysis the science and art of collaborative decision making - Raiffa, Howard (Cambridge Belknap Press of Harvard University Press, 2002)
This masterly book substantially extends Howard Raiffa's earlier classic, The Art and Science of Negotiation. It does so by incorporating three additional supporting strands of inquiry: individual decision analysis, judgmental decision making, and game theory. Each strand is introduced and used in analyzing negotiations.
Includes bibliographical references (p. [523]-530) and index.
Keywords: Negotiation in business